Cross-cultural analysis : methods and applications - Billiet, Jaak; Davidov, Eldad; Schmidt, Peter , 1942- (European Association of Methodology series, 2011)
The increasing availability of cross-national data sets allows researchers to engage in cross-cultural research more than ever. This resource bridges the gap between the methods and the applied research by presenting basic strategies for analyzing cross-cultural data, the methodological literature, and actual applications of the techniques